Therapeutic drug monitoring of levetiracetam in concomitant treatments - Damnjanović, Ivana (Archives of Pharmacy, 2022)
Levetiracetam (LEV) is one of the newer and most commonly used antiepileptic drugs. With its unique mode of action, LEV has proven effective in treating multiple seizure types, in both adults and children older than one month. It has been considered as an antiepileptic drug with an ideal pharmacokinetic profile, thanks to its rapid and complete intestinal absorption, negligible plasma protein binding, and non-hepatic metabolism. Due to its favorable profile, high degree of efficacy and low risk of interaction, it qualifies as a suitable candidate for concomitant antiepileptic treatments. Routine therapeutic monitoring of LEV concentrations is not common in clinical practice. However, despite the good tolerability and easy of dosing, recent research has focused on factors that may alter LEV pharmacokinetics. When considering concomitant antiepileptic therapy in which LEV is administered, growing number of studies highlights that altered pharmacokinetics of LEV can be expected in patients on polytherapy. Accordingly, special attention is paid to therapeutic monitoring of LEV during concomitant use with other antiepileptic drugs that induce or inhibit enzymes due to their potential effect on the pharmacokinetics of LEV. Since the pharmacokinetic profile of LEV may be influenced by many factors, the monitoring of concentration represent an important step in the individualization of the therapeutic approach necessary to control seizures without side effects. Accordingly, therapeutic monitoring of LEV may be useful in improving the outcome of concomitant antiepileptic therapy, as well as in patients with altered physiological conditions (pediatric and elderly patients, pregnant women with epilepsy).